Mechanical properties of mild steel (experiment and finite element analysis) - Nik Muhd Farhan Nik Saifuzaman (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Tensile test is one of the ways to study how strong a material. By leaving the damaged procedure, tensile test tend to be more accurate to compare it to other similar hardness test. The most of important in mechanical testing is techniques of strain measurement. A several of technique exists for measuring strain in the tensile test such as by machine crosshead motion and extensometer. These technique has its own advantages and disadvantages.